Surgical Outcomes of Contrast Sensitivity and Visual Acuity in Uveitis-Associated Cataract - Takeda, Atsunobu (Clin Ophthalmol, 2021)
PURPOSE: To evaluate the pre- and post-operative outcomes of phacoemulsification in patients with uveitis-associated cataract in remission, such as conventional visual acuity (VA), photopic and mesopic contrast visual acuity (CVA), and flares in the anterior chamber objectively assessed as intraocular inflammation. PATIENTS AND METHODS: This prospective study included 26 eyes of 19 patients with uveitis and 45 eyes of 26 controls who underwent cataract surgery at the Kyushu University Hospital and Kyushu Medical Center in Fukuoka, Japan, from October 2016 to December 2018. Conventional VA and flare values in the anterior chamber were evaluated preoperatively and 1 and 3 months postoperatively. Photopic and mesopic CVAs were assessed preoperatively and 3 months postoperatively. RESULTS: The best-corrected VA (BCVA) was improved significantly from baseline to 1 and 3 months postoperatively in both groups (P < 0.01 in both groups). The mean preoperative 100% and 10% CVAs under the photopic condition were significantly lower in the uveitis group than in the control group (P < 0.05 for both CVA), whereas the mean preoperative 100% CVA under the mesopic condition was comparable between the two groups. Although the mean preoperative 100% and 10% CVAs improved significantly from baseline under both photopic and mesopic conditions in both groups (P < 0.01 in both groups), the postoperative contrast sensitivities under both photopic and mesopic conditions remained lower in the uveitis group than in the control group (P < 0.01 for both conditions). The postoperative complications included recurrence of active inflammation in five eyes and cystoid macular edema in one eye and were managed by topical steroid therapy alone. CONCLUSION: Cataract surgery for uveitis-associated cataracts during remission is well tolerated. However, the present results suggest that amelioration of hemeralopia and/or nyctalopia is not as good as expected after cataract surgery in patients with uveitis.